Investigations of the DEAD-box helicase eIF4A - Phillips, Nicola Marie (2011)
Eukaryotic Initiation Factor (eIF) 4A is the most abundant initiation factor and the prototypical member of the DEAD-box family of helicases. Once recruited to the cap-binding complex, eIF4F, eIF4A unwinds inhibitory RNA secondary structure in the 5’ untranslated region (UTR) of mRNAs, promoting efficient ribosomal scanning to the start codon. The requirement for eIF4A in translation initiation correlates with increasing 5’ UTR length, suggesting that regulating the activity of eIF4A may affect the translation of particular mRNAs. It is well established that the transcripts of genes involved in cell cycle control and proliferation have long 5’ UTRs; therefore altering the activity of eIF4A may affect these genes specifically.